Sociocybernetic understandings of consciousness - Scott, Bernard CE (Journal of Sociocybernetics, 2018)
The aim of this paper is to show how sociocybernetics can usefully combine biological, psychological and sociological concepts to provide conceptual clarification and insightful understandings of human consciousness. Following a brief discussion and critique of how the term “consciousness” is used in contemporary cognitive science, awareness and consciousness are characterised in cybernetic terms as the dynamics of self-organising, autopoietic systems and their interactions. Sociocybernetic models of conscious systems are presented and discussed. It is argued that in order to characterise human consciousness it is necessary to make a distinction between bio-mechanical systemic unities and psychosocial systemic unities. Reflexively, this gives rise to a second-order cybernetics in which the observer explains herself to herself. Finally, there is a discussion of how sociocybernetic understandings of consciousness can give guidance for how to create and sustain communities in which good will prevails.
Keywords: consciousness; awareness; sociocybernetics